Domestic Violence among Pregnant Mothers in Northwest Ethiopia: Prevalence and Associated Factors - Berhanu Boru Bifftu; Berihun Assefa Dachew; Bewket Tadesse Tiruneh; Abarham Zeleke Zewoldie (Hindawi Limited, 2017)
Background. Domestic violence against women is a serious public health concern and human rights violation among pregnant mothers because of its negative effect on the life of both the mother and the fetus. Thus, the aim of this study was to assess the prevalence of domestic violence and associated factors among pregnant women. Methods. An institution based quantitative cross-sectional study was conducted among 418 women using a systematic random sampling technique. Binary logistic regression analysis and adjusted odds ratio with 95% confidence interval were used to identify the associated factors. Results. Overall, the prevalence of domestic violence was found to be 25.4%. Of this, the prevalence of psychological, physical, and sexual violence was 24.5%, 8.1%, and 2.4%, respectively. Low educational status (AOR = 4.59, CI: 1.496, 14.070), rural residency (AOR = 5.53, CI: 2.311, 13.249), unplanned pregnancy (AOR = 4.34, CI: 2.345, 8.020), and late initiation of antenatal care (AOR = 5.41, CI: 1.493, 19.696) were factors associated with domestic violence at p value < 0.05. Conclusion. Overall, more than quarter of the study participants had experienced domestic violence. Lower educational status, rural residency, unplanned pregnancy, and late initiation of antenatal care were factors associated with domestic violence. Thus, the authors suggest strengthening provision of women's reproductive health information.